Study of the 16S microbiome of swans died during the H5N1 outbreak in the Caspian seashore - Karamendin, Kobey; Nuralibekov, Sardor; Sabyrzhan, Temirlan; Kasymbekov, Yermukhammet; Suleymenova, Symbat; Kydyrmanov, Aidyn (Frontiers in Veterinary Science, 2025)
IntroductionIn 2023 and 2024, mass mortalities of swans occurred on the Caspian coast of Kazakhstan, which affected more than seven hundred birds of a local population of 10–15 thousand. It is widely known that viral infections significantly affect the microbiome content of various organisms, but the influence of H5N1 infection in the gut microbiota of wild birds remains little studied. Almost no information is available on postmortem microbial changes after the devastating impact of H5N1 influenza.MethodsIn addition to standard routine virological studies, we were interested in investigating the microbiological changes resulting from infection with the highly pathogenic H5N1 using 16S rRNA gene sequencing.ResultsVirological studies of samples taken from the dead swans identified the highly pathogenic influenza virus H5N1 subtype as the primary cause of mortality. 16S analysis of samples from freshly dead swans revealed patterns of microbial dysbiosis caused by the overwhelming dominance of Campylobacter and Fusobacterium genera in the microbiome.DiscussionUnlike previous fecal microbiome studies in live H5N1-infected birds, this is the first post-mortem analysis revealing systemic dysbiosis across respiratory and digestive tracts in swans, dominated by Campylobacter (mean 74.7% ± 19.3) and Fusobacterium (mean 15.9% ± 12.2).